Mountain memories : a pilgrimage of romance - Conway, Martin William (Cassel, 1920)
Alps -- Tirol -- The Engadine -- Pennine and Lepontine Wanderings -- Kashmir -- Himalayas -- Hispar Pass -- The Baltoro -- Ladakh -- The first crossing of Spitsbergen -- The Island Ice of Spitsbergen -- The Bolivian Andes -- South American Volcanos -- Fuegia